Währungsunion und deutsche Kapitalmarktzinsen - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
Since the negotiation of the Maastricht Treaty in December 1991 expectations on the new European currency could possibly influence European interest rates. The focus of this paper is both on the theoretical and empirical analysis of the link between European Monetary Union (EMU) and German interest rates. It is analysed how different views on the expected stability of the Euro should influence the German level of long-run interest rates, the German term structure and the French-German interest rate differential already before the start of EMU. After these theoretical considerations, the interest rate development between December 1991 and December 1995 is analysed by standard econometric methods. These results hint on the dominance of Euro-optimism in market expectations in the sense that interest rates in the Euro era are not expected to be different from interest rates in the DM era.
Keywords: 330